2005
DOI: 10.1103/physrevb.72.035426
|View full text |Cite
|
Sign up to set email alerts
|

Monotonically decreasing size distributions for one-dimensional Ga rows on Si(100)

Abstract: Deposition at room temperature of Ga on Si(100) produces single-atom-wide metal rows orthogonal to the Si-dimer rows. Detailed analysis using scanning tunneling microscopy reveals a monotonically decreasing size (i.e., length) distribution for these rows. This is unexpected for homogeneous nucleation without desorption, conditions which are operative in this system. Kinetic Monte Carlo simulation of an appropriate atomistic model indicates that this behavior is primarily a consequence of the feature that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…21. The unconventional shape of the scaled distribution function -monotonously decreasing -observed for 1D growth of Ga on Si(100) by Albao et al (and explained by means of KMC simulations using strongly anisotropic surface diffusion) 9 was theoretically investigated by Tokar and Dreyssé 11 . They showed that for equilibrium growth and a model with atomic interactions restricted to only nearest neighbors, the scaled distribution function is exponentially decreasing.…”
Section: Results Of Simulations and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…21. The unconventional shape of the scaled distribution function -monotonously decreasing -observed for 1D growth of Ga on Si(100) by Albao et al (and explained by means of KMC simulations using strongly anisotropic surface diffusion) 9 was theoretically investigated by Tokar and Dreyssé 11 . They showed that for equilibrium growth and a model with atomic interactions restricted to only nearest neighbors, the scaled distribution function is exponentially decreasing.…”
Section: Results Of Simulations and Discussionmentioning
confidence: 92%
“…Similarly as in the model used by Albao et al 9 arrangement of atoms in chains into dimers is not taken into account.…”
Section: Simulation Modelmentioning
confidence: 99%
“…A quick survey of the literature provides us with numerous examples: Mg/Si(557) 59 , Si/Si(001) 60 , Mn/Si(001) [61][62][63][64][65] , CoSi 2 /Si 66 , Ga/Si(001) [67][68][69][70] , Sr/Si(111) 71 and Sr/Si(001) 72 , Ag+Au/Si(557), 44 Ir/Si(001) 73 , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of such chains of varying lengths has been observed in some heteroepitaxial systems. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] From the point of view of applications, it would be desirable that the chains were of similar length and regularly spaced. Therefore, the understanding of the mechanisms which define the chain sizes and interchain spacings would be of considerable interest.…”
mentioning
confidence: 99%